A Mass Ratio of Hierarchical H-ZSM5 And Fatty Acid Methyl Ester of Cerbera Manghas Oil and The Effect on The Hydrocarbon Liquid Product Composition - Sutrisno; Rahmi, Rahmi; Marlinda, Lenny; Muttaqii, Muhammad Al; Afrila, Cyndy Dwi; Fasmawi, Yanuar; Evrianti, Yuli (IPTEK The Journal for Technology and Science, 2025)
Fossil fuels are classified as non-renewable resources. On the other hand, using fossil fuels has further aggravated the impact of the environmental crisis. The development of alternative fuels that are renewable and sustainable is urgently needed in line with the increasing need for fuel. One alternative energy source that can be used in the development of biofuels is Cerbera manghas oil. The catalytic cracking process with 178 grams of Cerbera manghas oil can be carried out using hierarchical H-ZSM-5 as a catalyst with a mass of 0.1, 0.2, 0.3, 0.4, and 0.5 grams at a temperature of 250 degrees Celsius. Gas Chromatography–Mass Spectrometry (GC-MS) analysis was performed on Cerbera manghas oil and biofuel products. Several hydrocarbons, C7 to C12 and C16 to C17, with the largest content, were identified as diesel (29.14 percent) and gasoline (14.08 percent) using a catalyst mass of 0.5 grams. Therefore, the use of hierarchical H-ZSM-5 catalyst in the catalytic cracking of Cerbera manghas oil can produce hydrocarbon compounds in the gasoline range.